Potential of conservation agriculture practice in climate change adaptation and mitigation in Ethiopia: a review - Hailu, Leta; Teka, Wondimagn (Frontiers in Climate, 2024)
Land degradation is a major problem in Ethiopia, as it contributes to climate change by releasing greenhouse gases (GHG) and slowing carbon sequestration rates. The objective of this review was to assess the role of conservation agriculture (CA) in climate change adaptation and mitigation in Ethiopia. The critical review method processes for identifying and synthesizing peer-reviewed research and review articles, reports, proceedings, and book chapters were followed, with materials obtained from relevant search engines. The findings of the various reports revealed that minimum tillage assists in soil moisture conservation when compared to conventional tillage. Conservation tillage maintains crop residue, reduces soil temperature significantly, and increases nutrient buildup in the surface soil layer, all of which lead to higher crop growth and production thus help as adaptation to climate change. Furthermore, agriculture and other land uses significantly contribute to greenhouse gas emissions; nevertheless, conservation agricultural methods improve soil organic carbon (SOC), soil aggregation, and carbon in aggregate, as well as soil health that contribute to climate changing mitigation. Several studies found that soil health indicators such as soil aggregation, soil organic carbon storage, soil enzymes, and microbial biomass improved under conservation tillage practices, potentially improving the carbon-nitrogen cycle, soil stability, and overall crop productivity. In terms of climate adaptation and mitigation, CA is one of the non-substitutable choices for reducing greenhouse gas emissions. Crop diversity, increased nitrogen consumption efficiency, crop rotation, improved soil carbon sequestration methods; crop residue retention, minimum soil disturbance, manure incorporation, and integrated farming systems are all important factors in minimizing GHG emissions. Moreover, factors impeding CA adoption include a lack of appropriate equipment and machinery, weed control methods, the use of crop residue for fuel wood and animal feed, a lack of awareness about the benefits of CA on soil health and sustainability, and a lack of government technical and financial support for smallholder farmers. Adoption and scaling up of CA practices are critical for ensuring a sustainable development goal and resilient future. Thus, relevant stakeholders should consider the aforementioned considerations while promoting the technology on a large scale through integration with enhanced technology.